Primary male urethral squamous cell carcinoma presenting with a genital abscess. Issue 4 (13th June 2019) - Mizusawa, Hiroya; Hara, Hiroaki; Mimura, Yuji; Kato, Haruaki
Abstract : Introduction: Primary urethral cancer is a rare disease accounting for <1% of all urological cancer cases. We encountered a patient with urethral squamous cell carcinoma diagnosed during treatment of a genital abscess. Case presentation: A 69‐year‐old male was referred to our hospital for recurrent urethritis and swelling of the scrotum. The genital skin was atrophic with a purulent discharge. A diagnosis of epididymitis‐induced genital abscess was made, and conservative treatment was administered. However, local infection recurred and the infected tissue was resected 4 months after the first examination. The pathological diagnosis was squamous cell carcinoma. Subsequently, radical surgery was performed, but the patient died 17 months postoperatively. Conclusion: Four patients with primary urethral squamous cell carcinoma presenting as genital abscess have been reported. Careful examination is necessary while considering a malignant tumor as an underlying disease.